The Influence of Work Professionalism on Employee Performance at PT. PNM Kabanjahe Branch - Heru Setiawan, Dwi; Isa Indrawan, Muhammad; Farida Ferine, Kiki (International Conference Epicentrum of Economic Global Framework, 2025)
This study aims to analyze the influence of work professionalism on employee performance at PT. PNM Branch Kabanjahe. Employee performance is an important factor in supporting organizational effectiveness, especially in service-based financial institutions that require discipline, responsibility, and high work commitment. Professionalism is considered one of the factors that can improve employee performance through better work attitudes, integrity, and compliance with organizational standards. This research employed a quantitative approach using explanatory research methods. The population of this study consisted of all employees of PT. PNM Branch Kabanjahe, totaling 50 employees. Since the population size was relatively small, the study used a saturated sampling technique, in which all employees were selected as respondents. Data were collected using questionnaires distributed directly to respondents and analyzed using Jamovi statistical software. The data analysis techniques included descriptive statistics, validity tests, reliability tests, normality tests, simple linear regression analysis, and coefficient of determination analysis. The results of the study showed that work professionalism had a positive and significant effect on employee performance. The regression analysis indicated a significance value of 0.000, which was smaller than 0.05, meaning that professionalism significantly influences employee performance. The coefficient of determination (R²) value was 0.561, indicating that work professionalism contributed 56.1% to employee performance, while the remaining 43.9% was influenced by other variables outside this study. The findings indicate that employees with high professionalism tend to demonstrate better discipline, responsibility, integrity, and commitment to work quality, leading to improved employee performance. Therefore, PT. PNM Branch Kabanjahe is expected to continuously improve employee professionalism through organizational culture strengthening, discipline improvement, and employee development programs.